Cerebral Artery Aneurysm Masquerading as Ptosis in a Child - Parajuli, Sanket; Shrestha, Pooja; Koirala, Sunita (Nepalese Journal of Ophthalmology, 2018)
An 8-year-old female presented to Eye OPD of Dhulikhel Hospital, Kathmandu University Hospital, with drooping of the right upper lid and inability to move right eye ball since 3 days. She had no history of trauma or fall injury. On ocular examination, visual acuity was 6/6 on both eyes and there was severe ptosis on the right eye in which eyeball remained abducted with restriction of ocular motility on all gazes. The pupil was dilated and 6mm on the right eye in room light. Posterior segment examination was normal. MRI angiography was done which revealed a right Posterior cerebral artery aneurysm.